Contribution of reduced skeletal muscle perfusion reserve to exercise intolerance in heart failure with preserved ejection fraction - Serafin, Adam; Jasic-Szpak, Ewelina; Marwick, Thomas H.; Przewlocka-Kosmala, Monika; Ponikowski, Piotr; Kosmala, Wojciech (International journal of cardiology, 2024)
Skeletal muscle (SM)-associated mechanisms of exercise intolerance in HFpEF are insufficiently defined, and inadequate augmentation of SM blood flow during physical effort may be one of the contributors. Therefore, we sought to investigate the association of SM perfusion response to exertion with exercise capacity in this clinical condition. Echocardiography and SM microvascular perfusion by contrast-enhanced ultrasound were performed at rest and immediately post-exercise test in 77 HFpEF patients in NYHA class II and III, and in 25 subjects with normal exercise tolerance (stage B). Exercise reserve of cardiac function and SM perfusion was calculated by subtracting resting value from exercise value. In addition to decreased cardiac functional reserve, HFpEF patients demonstrated significantly reduced SM perfusion reserve as compared to HF stage B, with the degree of impairment being greater in the subgroup with more profound left ventricular (LV) diastolic abnormalities (E/e’ > 15 and TRV > 2.8 m/s). SM perfusion reserve was significantly associated with exercise capacity (beta = 0.33; SE 0.11; p = 0.003), cardiac output reserve (beta = 0.24; SE 0.12; p = 0.039), resting E/e’ (beta = −0.33; SE 0.11; p = 0.006), and patient frailty expressed by the PRISMA 7 score (beta = −0.30; SE 0.11; p = 0.008). In multivariable analysis including clinical, demographic and cardiac functional variables, SM perfusion reserve was in addition to patient frailty, sex and LV longitudinal strain reserve among the independent correlates of exercise capacity. SM perfusion reserve is impaired in HFpEF, and is associated with reduced exercise capacity independent of clinical, demographic and “central” cardiac factors. This supports the need to consider the SM domain in patient management strategies in HFpEF. •Skeletal muscle (SM) perfusion reserve during physical effort is impaired in HFpEF.•SM perfusion reserve is independently associated with exercise capacity in HFpEF.•SM domain might be considered in patient management strategies in HFpEF.